IMMUNOMODULATORY EFFECTS OF BLACK CINCAU (MESONA PALUSTRIS BL.) SUPPLEMENT ON ESCHERICHIA COLI STRAIN O157-INFECTED MICE - Widyaningsih, Tri Dewanti; Martati, Erryana; Lukitasari, Diah Mustika (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â Â Objective: This study objective was to determine the immunomodulatory effects of the black cincau (Mesona palustris BL.) supplement on Escherichia coli strain O157-infected mice. Methods: Black cincau (Mesona palustris BL.) and red ginger (Zingiber officinale var. rubrum) were extracted on a pilot plant scale. For the animal experiment, the mice were adapted for 7 days with black cincau supplement at a dose of 43.29 mg/kg b.w. (SSP I), a dose of 85.58 mg/kg b.w. (SSP II), a dose of 4.33 mg/kg b.w. of a commercial immunomodulator (SK) and buffer saline for the negative control (KN) and positive control (KP). Then, mice were infected intraperitoneally (intraperitoneally) with E. coli strain O157 1010 cfu/mL, except KN. On day 21, the cell of mouse spleen was analyzed using flow cytometry. Results: Result showed that administration of black cincau supplement up to 85.58 mg/kg b.w gave immunomodulator effects in infected mice. Immunomodulator effect can be seen through the increasing of the relative average of a cluster of differentiation (CD)4+ T cells, CD8+ T cells, CD4+ CD8+ T cells, CD4+ CD62L T cells, CD8+CD62L T cells, and CD68+interferonÎ³ (Interferon gamma) monocytes cells. Exposure of black cincau supplement on infected mice can recover small intestine mucosa structure of mice. Conclusions: This study demonstrates that the supplement of black cincau extract can give an immunomodulatory effect on E. coli-infected mice.